Expression levels and diagnostic value of serum GDNF, CEA and CA199 in patients with Colorectal Carcinoma: Serum biomarkers for colorectal cancer diagnosis - Wang, Jue; Liu, Lulu; Zheng, Yan; Gu, Sai (Journal of Medical Biochemistry, 2023)
Background: To investigate the expression levels and diagnostic value of glial cell line-derived neurotrophic factor (GDNF), carcinoembryonic antigen (CEA) and carbohydrate antigen199 (CA199) in patients with colorectal carcinoma (CRC). Methods. 50 CRC patients at our hospital from Feb. 2020 to Feb. 2021 were chosen as the malignant group, another 50 patients with benign colonic diseases were chosen as the benign group, and 50 healthy people who came to our hospital for physical examination during the same period were considered as the control group. Fasting peripheral venous blood was taken from all research subjects in the morning and tested by a fully-automated electrochemiluminometer to determine the GDNF, CEA and CA199 levels. The sensitivity and specificity of the combined detection of the three indexes for CRC were analyzed, and the ROC curve was plotted to record the area under the curve (AUC). Results. The malignant group had remarkably higher CEA and CA199 levels (P
Keywords: GDNF; CEA; CA199; Colorectal carcinoma (CRC); Diagnostic value